Correction: Jin et al. Influence of the Nocturnal Effect on the Estimated Global CO2 Flux. Remote Sens. 2022, 14, 3192 - Rui Jin; Tan Yu; Bangyi Tao; Weizeng Shao; Song Hu; Yongliang Wei (Remote Sensing, 2022)
We believe that several sentences in the description of the source (sink) changes of CO2 are prone to ambiguity and are not particularly well presented [...]